Efficacy of α-blocker in improving ureteral stent-related symptoms: a meta-analysis of both direct and indirect comparison - He F; Man LB; Li GZ; Liu N (Dove Medical Press, 2016)
Feng He, Li-bo Man, Gui-zhong Li, Ning Liu Department of Urinary Surgery, Beijing Jishuitan Hospital, Beijing, People’s Republic of China Objective: To critically evaluate the efficacy of an α-blocker in improving ureteral-stent-related symptoms and preliminarily investigate the difference between different types of α-blockers. Methods: Relevant randomized controlled trials were identified through searching PubMed, the Cochrane Library, Embase, and other sources. After quality assessment and data abstraction, direct comparison based on the Ureteral Stent-related Symptom Questionnaire (USSQ) between α-blockers and control was performed by RevMan 5.3. Indirect comparison between different types of α-blockers was performed by ITC 1.0. Sensitive and subgroup analyses were used to handle important clinical factors. Results: Sixteen randomized controlled trials containing 1,489 cases were included. Compared with control, α-blockers significantly reduced the overall urinary symptom, pain index, general health index, and scores related to sexual matters, while no significant difference was found in work performance and additional problem scores. Subgroup analysis showed that the duration of stent insertion, patient’s age, stent size, and the type of α-blocker had the potential to influence the outcomes. Through indirect comparison, we found alfuzosin and terazosin to be better than tamsulosin in pain relief and general health improvement. Conclusion: α-Blocker was effective in treating ureteral stent-related symptoms, as it improved the major indexes of USSQ post-insertion or post-removal. Alfuzosin and terazosin seemed to be better than tamsulosin, which needs further verification because of the lack of direct comparison currently. Keywords: α-blocker, tamsulosin, alfuzosin, terazosin, ureteral stent-related discomfort